Pengaruh Model Pembelajaran Quantum Learning Terhadap Hasil Belajar IPA Siwa Kelas 1V SDN 3 Pijot Tahun Pelajaran 2019/2020 - Salihin, Muhammad (FAKULTAS TARBIYAH, 2020)
This study aims to determine the effect of the Quantum Learning Model on the Science Learning outcomes of students in Class 1V at SDN 3 Pijot. 2019/2020 Academic Year. with a sample of 32 students from class IVa and 30 class 1Vb. This type of research uses a quasi-experimental design in the form of a control group pretest-posttest design. The research instrument used a multiple choice test. How to collect data using pretest and posttest and analyzed using Product moment correlation test. After comparing the results of the pretest and post-test data, the results showed that there was an increase in student learning outcomes and performance, namely 17.7% with a correlation test obtained t-count = 3.348 and t-table = 1.671 at the use of the 99% confidence interval level with the coefficient of influence including the very high category. So the conclusion is that there is an influence of the Quantum Learning Learning Model on the Science Learning Results of Students Class 1V at SDN 3 Pijot. 2019/2020 Academic Year